Taxonomic and ultrastructural study of the genera Strombomonas and Trachelomonas (Euglenophyta) from Colombia - Tolivia, Analía Alejandra (2024)
A floristic and ultrastructural study on loricated Euglenophyta was made in several freshwater bodies from the Amazonian and Caribbean regions of Colombia. A total of 114 taxa were recorded, 93 belonged to the genus Trachelomonas Ehr., and 21 to Strombomonas Defl. From the total taxa determined, 73 were recorded for the first time for Colombia, 19 for the Amazonian and 52 for the Caribbean region. Besides 43 taxa were examined by scanning electron microscopy (SEM) and details of its ultrastructure are illustrated.